Longitudinal and lateral circulation and tidal impacts in salt-plug estuaries - Hosseini, Seyed Taleb; Stanev, Emil; Pein, Johannes; Valle-Levinson, Arnoldo; Schrum, Corinna (Frontiers in Marine Science, 2023)
This study presents a comparison of forcings between density gradient and tides in idealized funnel-shaped salt-plug estuaries. Three-dimensional numerical model results also examine longitudinal and lateral circulations. In salt-plug estuaries, a positive longitudinal estuarine circulation is observed landward of a salinity maximum zone or salt plug. Seaward of the salt plug, the estuary shows an inverse circulation cell. The longitudinal flows show a fortnightly variability inside the salt plug. Also, the salt plug is saltier in spring tides than in neap tidal cycles mainly owing to higher landward salt transport by tidal advection during the spring tides. The lateral circulation and divergence dv/dy have the influence of Coriolis acceleration. In the absence of Earth’s rotation, the tidally averaged lateral circulations have nearly the same directions within the positive and inverse cells. Directions of lateral flow reverse in the salt-plug area. Inside this area, the lateral circulation also shows clear neap–spring variability, including downwelling cells during spring tides and upwelling in neap tides. The salinity maximum zone exhibits a vertically homogeneous condition particularly in meso-tidal salt-plug estuaries. Finally, this study introduces the threshold of “log(tidal Froude number)=3” (tidal forcing 3 orders of magnitude ≥ density gradients) for salt-plug estuaries as the condition under which the tidal forcing can overcome the density gradient, and consequently salinity inside the salt plug zone is reinforced by tides with a landward movement. This robust salinity maximum zone is also identified by a high Ekman number (log(Ekman number)>0.25).